KESANTUNAN IMPERATIF DALAM NOVEL DUA GARIS BIRU KARYA LUCIA PRIANDARINI - Diah Mulyani; Ahmad Rabi ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractThis research is based on knowledge of impartial speech in the novel Dua GarisBiru. The formulation of the problem in this research is how is the existence ofimperative politeness in the novel D by Lucia Priandarini, the pragmatic meaning ofthe imperative, and the imperative modesty markers. The purpose of this study is todescribe the impressionism of imperative speech in Lucia Priandarini's novel DuaGaris Biru, which is divided into imperative politeness, imperative pragmaticmeaning, and imperative politeness. The method used is descriptive method. Theform of research is qualitative research. The data collection technique is adocumentary study technique. The results of the data analysis contained 42 forms ofimperative politeness. The pragmatic meaning of the imperative amounts to 126 datawhich is divided into 16 words of speech commands, 18 command , 19 request, 24application, 2 persuasion, 8 encouragement, 2 encouragement, advice, 4 expletivewords, 6 hope, 12 prohibition, 3 permission, 7 request for permission, 2 remarks, 3remarks. There are 25 imperative guideline markers divided into 4 signs ofpoliteness, 6 signs of modesty, 4 signs of politeness, 4 signs of politeness, 4 coming,1 sign of politeness, 1 sign of politeness, 3 signs of politenessKeywords: Pragmatic, Imperative, Novel